Inovasi Sekolah Umum Negeri Model PAI - Yuliana Habibi (Madaniyah, 2017)
This study reviews implementation of SK Walikota Pekalongan on PAI Model State Public School (Study in SDN Panjang Wetan 02 Pekalongan), with a qualitative descriptive approach. This research was motivated by the learning process is distinctively its own SDN Panjang Wetan 02 Pekalongan as a model school PAI. The learning process as it was interesting, because it rarely exists in every elementary school state schools. There are four reasons the learning model that is ideal reasons, constitutional, structural, and cultural. Learning practices at SDN Panjang Wetan 02 Pekalongan as the implementation of SK Walikota is: reading the Qur’an / Qiro'ati starting at 06:30, followed invocation wirdu ash-shabaah, learning of course materials by integrating the values aqidah- akhlaq, utilizing the first break time for sholat dhuha for a particular class, sholat berjamaah in congregation, and development / TPQ deepening of PAI in school before returning home, and it all ends with a prayer.